Geo-Congress 2020. selected papers from sessions of Geo-Congress 2020 : February 25-28, 2020, Minneapolis, Minnesota - Hambleton, James P.; Makhnenko, Roman; Budge, Aaron S. 1974- (American Society of Civil Engineers, 2020)
The fourth of seven volumes containing the full collection of papers presented at Geo-Congress 2020: Vision, Insight. This volume contains 97 peer-reviewed papers on geotechnical earthquake engineering and other special topics. Topics include: soil dynamics and earthquake engineering; rock mechanics; pavement modeling and composition; geotechnics of coasts, oceans, ports, and rivers; U.S.-Canada shared geotechnical issues; and geo-education. GSP 318 will be of interest to practitioners and researchers working is all aspects of earthquake engineering
Keywords: Geotechnical engineering -- Congresses.; Earthquake engineering -- Congresses.; Soil dynamics -- Congresses.; Pavements -- Performance -- Congresses.; Coastal sediments -- Congresses.; elektronické knihy; electronic books